Development and Validation of Teaching and Learning Module Based on Addie Model for Year 4 Plant Topic - Afif Bin Mohd Aris, Muhammad; Binti Mansor, Rosnidar (International Journal of Academic Research in Progressive Education and Development, 2023)
Experiment activity is an important tool in learning process, especially experiment that are made based on student needs and characteristics. One of common problems to apply experiment in teaching and learning session is lack of complete laboratory in school. This study aims to produce and determine the feasibility of teaching and learning module for plant topic for fourth grade primary school students. The research method was used R&D (Research and Development) using ADDIE model. The ADDIE model consists of analysis, design, development, implementation, evaluation. Based on the results of research (1), the teaching and learning module for year 4 students plants topic is produced. (2) The overall agreement percentage obtained from the experts is 90.44%. From the result, the content validity analysis of the ADDIE-based teaching and learning module by 6 experts shows a good score with an average expert agreement percentage of 88%. (3) The alpha Cronbach was obtained from the reliability valued at 0.897. The results of the feasibility questionnaire analysis show very good values of 90.44%. Thus, the teaching and learning based on ADDIE module for year 4 students plants topic is suitable for use as a learning medium for primary school students.